Modernism after postcolonialism : toward a nonterritorial comparative literature - De Gennaro, Mara, 1972- (Hopkins studies in modernism., 2020)
"Many previous studies of modernity read colonial or postcolonial texts through the lens of critical theories originating in Europe or North America, but author Mara de Gennaro undertakes a comparative literary approach in which she juxtaposes a canonical anglophone modernist writer with an anglophone or francophone postcolonial writer. She models a new critical approach for relating modernism to postcolonialism"--